Penyusunan Peta Konsep Mempermudah Belajar Siswa Selama Masa Pandemi Covid-19 - Rahmat Syawaludin; Sutama Sutama (Universitas Muhammadiyah Surakarta, 2020)
Based on some research, mind mapping proven effective to use in the class, but the use of mind mapping still rarely used in the class during pandemic. The purpose of this article is 1) to analyze of making mind mapping; 2) to describe the using of mind mapping during this pandemic; and 3) to analyze the impact of using mind mapping in class. This article uses literature study. The validity of this data is by using some study from another research with an extension time. Data comparation is used as data analysis technique in this article. The conclusion in this article are 1) while making mind mapping, requires some laws so that benefit would achieved optimally; 2) using mind mapping with outlines and good instruction about material is a good option during pandemic; 3) using of mind mapping is proven effective to make student easier to know about the material and it will improve their critical thinking skills.